Nature—Inspired Flow Patterns for Active Magnetic Regenerators Assessed Using a 1D AMR Model - Navickaitė, Kristina; Bahl, Christian; Engelbrecht, Kurt (Frontiers in Energy Research, 2019)
A novel flow structure of a solid active magnetic regenerator is proposed in this paper. The numerical performances of two nature-inspired flow geometries, based on double corrugated tubes with an elliptical cross-section, are compared to the performance of conventional flow structures for Active Magnetic Regeneration (AMR) applications, namely, packed spheres and a cylindrical micro-channel matrix. The numerical performance of all the geometries is analysed in terms of cooling power and coefficient of performance. Regenerators with various porosities and two different hydraulic diameters of the flow channels are evaluated varying utilisation at fixed temperature spans between the hot and cold reservoirs. The selection of the regenerator geometry is based on two actual AMR machines. The numerical results demonstrate that a suitably optimized AMR geometry with a double corrugated flow pattern provides the same or higher efficiency at higher porosity compared to conventional AMR flow geometries. These findings suggest that the magnetocaloric material used to construct AMR beds can be exploited more efficiently and at a lower investment cost of an AMR device when suitable double corrugated flow pattern is used.